Service Potential Analysis Of Passenger Train Operations On Medan – Belawan Route In Order To Develop Northern Medan Region - sembiring, Eli Daniel; Sirojuzilam; Purwoko, Agus (Journal of Environmental and Development Studies, 2022)
The strategy to overcome traffic jam in Medan City is by using train transportation mode. PT. Kereta Api Indonesia (Persero) Regional Division I of North Sumatera as the operator has operated passengers train with Medan-Belawan route, however the train only operated for 2 years (2010-2011). The objective of the research is to analyze potential of passenger train, revenue of train operator, feasibility of train project investment, as the effort to re-operate passenger train. Based on analysis result, it can be concluded that a concept of transit oriented development (tod) around the Belawan station is required to increase potential of total passengers